Soil enzyme activities under pig slurry addition and different tillage systems - doi: 10.4025/actasciagron.v33i4.9816 - Balota, Elcio Liborio; Machineski, Oswaldo; Truber, Priscila Viviane (Acta Scientiarum. Agronomy, 2011)
The objective of this work was to evaluate the changes in soil enzyme activities due to application of pig slurry under different soil tillage systems. The experiment was conducted in a clayey Oxisol in Palotina, PR, using different quantities of pig slurry (0, 30, 60 and 120 m3 ha-1 year-1) applied to the soil prior to the summer and winter crop season under conventional tillage (CT) and no tillage (NT), with three replicates. The areas were cultivated with soybean (Glycine max L.) and maize (Zea mays L.) in the summers of 1998 and 1999, respectively, and with wheat (Triticum sativum Lam.) in the winters of both years. The soil samples were collected in March and October of 1998 and 1999 at depths of 0-5, 5-10 and 10-20 cm. The pig slurry application and the soil tillage systems influenced enzyme activities in the soil. The increase of pig slurry application decreased the ratio of soil enzyme activities to microbial biomass carbon. The phosphatase activity had a negative relationship with soil-available phosphorus. The acid phosphatase activity decreased both under CT and NT systems at all depth studied due to pig slurry application.